Sport events tourism: an approach to the Portuguese case - Palrão, T. (2017)
Sports events assume a major importance in tourism. This relevance results particularly from the fact that there are numerous disciplines that can be practiced and nowadays tourists are traveling around the world to participate in multiple sport events. Considering that, it becomes imperative to study the different types of involvement that tourists may have in all of the involved processes. Particularly, Portugal is a country holding excellent natural conditions for Tourism and for the practice of a considerable number of different sporting activities, many of them possible to be held all year round. This study´s intention is to define a framework model which will allow the understanding of the main touristic motivations for tourists’ participation in sports events activities, particularly considering the Gammon & Robinson’s (1997) classification and Weed & Bull (2004). The main objective of the study is to create a consistent theoretical basis for the study of these events. There is already a possible outcome for the study based on its present stage resulting that, according to either the responsible agents for the sector and the ones for the specific described events, sports events in Portugal have been increasing and that Portugal is being much demanded for this kind of events.